2019
DOI: 10.1177/1558925019865697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical, chemical and biological extraction methods on the physical behaviour of banana pseudo-stem fibres: Based on fibres extracted from five common Sri Lankan cultivars

Abstract: This article presents the strength, diameter, elongation and tenacity variations of banana pseudo-stem fibres extracted from five common Sri Lankan cultivars. The banana plants that were selected represent the dry and wet climatic zones of Sri Lanka. Mixtures of all layers of stem from the selected cultivars were subjected to three different extraction methods. Decortication technique was used for mechanical extraction, sodium hydroxide was used for chemical extraction and pectinase enzyme was used for biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Sodium hydroxide (NaOH) is popularly used to reduce the fiber roughness, but also produces good quality fiber. Reagents such as sulfuric acid, hydrogen peroxide, protease and sodium citrate can also be used for chemical extraction [23].…”
Section: Other Methodsmentioning
confidence: 99%
“…Sodium hydroxide (NaOH) is popularly used to reduce the fiber roughness, but also produces good quality fiber. Reagents such as sulfuric acid, hydrogen peroxide, protease and sodium citrate can also be used for chemical extraction [23].…”
Section: Other Methodsmentioning
confidence: 99%
“…These processes may cause contamination of the environment because of the need to treat the residues produced. 23 Metabolic pathways are eco-friendlier and produce more fibre bundles. Ganan et al 24 reported extraction of banana fibres using natural biological retting.…”
Section: Structural and Chemical Composition Of Banana Fibrementioning
confidence: 99%
“…2 fibres/yarns in particular are selected as the reinforcing material due to the abundant availability, ease of manufacturing and most importantly, renewability. Banana is the most planted tree in Sri Lanka (469 842 tons/year, 49,168 hectare) and its fibres have been used in yarn manufacturing (Mumthas et al, 2019, Balakrishnan et al, 2019.…”
Section: Introductionmentioning
confidence: 99%